How does buoyancy influence front-crawl performance? Exploring the assumptions - Yanai, T.; Wilson, B. D. (Sports Technology, 2008)
A new theoretical framework for understanding the influence of buoyancy on swimming performance is proposed in this paper. During front-crawl swimming, the hydrodynamic force acting on the hands generates the leg-sinking moment around the center of mass, which is counteracted by the leg-raising moment generated by the buoyant force.